PENGARUH ASSET INTENSITY DAN DEBT POLICY TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG BERGERAK DI BIDANG PERTAMBANGAN TERDAFTAR DI BURSA EFEK INDONESIA PERIDOE 2011-2020 - Ponirah, Ade (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2021)
Taxes are a source of cash income for the state. Taxes are levied on taxpayers with applicable provisions. One of the largest contributors of tax receipts is from corporate taxpayers. Tax avoidance is part of an active effort to fight taxes, all actions taken directly to avoid taxes. Asset intensity is a long-term asset and this asset is operational support of the company and will not be sold. A debt policy is a policy determined by the company to meet the needs of funds derived from debt. This research uses descriptive methods and quantitative approaches using secondary data supported by literature and documentation studies. The results showed that partial asset intensity had no significant effect on tax avoidance. Similarly, debt policy has no significant effect on tax avoidance. Simultaneously asset intensity and debt policy have an insignificant effect on tax avoidance with a contribution of 22%. Keywords: Asset Intensity, Debt Policy, Tax Avoidance